Songbird : a solo collection [compact disc] - McVie, Christine (Rhino, 2022)
First ever compilation from rock & roll hall of famer highlights songs from her solo career, newly remastered by Glyn Johns, along with two unreleased studio recordings. Also includes new orchestral version of Fleetwood Mac classic "Songbird".